A Model of the Best Private University Selection in Aceh. Issue 1 (February 2020) - Taufiq,; Zarlis, Muhammad; Mawengkang, Herman; Suwilo, Saib
Abstract: The Integrated Population Decision Support Model in the village needs to be developed according to the rules of Law number 6 of 2014 with a decision information system model that can assist one in making accurate and targeted decisions in choosing a university. Many problems can be solved using a model, one of which is the Decision Making System, for the Determination of Human Resources in an area. There are several models that have been built including Analytical Hierarchy Process (AHP). which is the most widely used research method in solving multi-criteria problems, such as in the Determination of Human Resource Selection. This research model uses Analytical Hierarchy Process (AHP) in determining the University for a superior place of learning for human resources. In determining the University, there are several basic decision-making, including the place of the educational model, the model of expertise / skills taught, reputation, quality, teaching and learning process. The final results in this study are the priority results of university criteria, which are sorted from highest to lowest, so that prospective student users who wish to continue their higher education in choosing a regional university (rural) can easily make decisions by determining the university in the village which, and finally this model is almost 80% accurate.